Chert exploitation and circulation in eastern Lombardy (Northern Italy): a diachronic overview through prehistory - Stefano Bertola; Domenico Lo Vetro; Paolo Schirolli; Federico Confortini; Matteo Malzanni; Pasquino Pellecchi (UISPP Journal)
This work focuses on the Eastern Lombardy Prealps (central Southern Alps), including the Brescia and Bergamo provinces. Knappable lithic raw materials are represented by cherts and radiolarites which are quite common in the Jurassic-Cretaceous sedimentary series. Tectonics played an important role for the preservation of good chert outcrops. Several prehistoric sites are located not far away from the primary lithic sources; in particular we have identified three main areas with good outcrops. South-north mobility along the main valleys is highlighted by the raw materials displacements from the outcrops, situated at the mouth of the valleys, to the north. The Palaeolithic record of the area is very poor. Mousterian sites are generally located near the outcrops. An Epigravettian site is situated far away from the primary sources in the mid-mountain easily accessible by valley routes. A greater mobility is documented in the Mesolithic when also extra-regional cherts (western Trentino) were introduced in the sites. In the Brescia district, starting from the Neolithic and during the Copper age, we observe an increase in the import of very good chert types from the Baldo/Lessini area for specific purposes together with the exploitation of the local resources for domestic use.